Presensi Karyawan Berbasis Web dengan Fitur Lokasi Leaflet JS menggunakan Laravel - Indah Adinda Marleni; Aris Gunaryati (KITA Institute, 2023)
Technological developments are increasingly sophisticated and along with the times, are able to summarize and simplify human work. Especially in managing attendance manually by recording on an attendance sheet, it will take a long time and entering attendance data one by one. It is possible that an error occurred in the data input process. So, humans take advantage of technology by developing attendance applications that can detect employee presence online that can be connected to the website. With this, the author creates a system for implementing web presence applications, with the Map Leaflet JS Location features by using Laravel which can help calculate employee absences in real time and is able to detect employee locations accurately. This Web Application System, The Extreme Programming design method uses the PHP programming language, MySQL database and Laravel Framework. This Web Application System can be equipped with employee data pricessing features, employee leave permission data to. In order to be able to provide employee absence information and print reports related to employee attendance information.